PENGARUH KUALITAS PRODUK, DISTRIBUSI, DAN DIGITAL MARKETING TERHADAP KINERJA PEMASARAN UMKM KULINER LOKAL PECAK BANDENG KOTA SERANG DI MASA PANDEMI - Hafilda, Siti Azky; Meutia, Meutia Meutia; Bukhari, Ahmad (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2021)
This study aimed to identify the influence of product quality, distribution and digital marketing towards the marketing performance of the UMKM of pecak bandeng as local culinary in pandemic era. The kind of data used in this study is the primary data based on questionnaires given to the owners of pecak bandeng UMKM in Serang city which have used digital marketing. The measurement techniques using likert scale 1-5 and tested with the validity and reliability. The data analysis technique used to answer a hypothesis is multiple linear regression analysis. The results of this study showed that product quality, distribution and digital marketing have an influence on the marketing performance with a significance value 0.00 < 0.05. The result means that H0 was rejected and H1 was accepted. And the result means the coefficient of determination indicates product quality, distribution and digital marketing has an influence towards the marketing performance is 96% while the rest 4% influenced by other factors.